Interactions of tenofovir and tenofovir disoproxil fumarate with drug efflux transporters ABCB1, ABCG2, and ABCC2; role in transport across the placenta - Neumanova, Zuzana; Cerveny, Lukas; Ceckova, Martina; Staud, Frantisek (AIDS (London, England), 2014)
OBJECTIVE AND DESIGN: Tenofovir (TFV) is used in pregnant women as a part of combination antiretroviral treatment to prevent mother-to-child transmission of HIV infection. We aimed to detect whether TFV and/or its prodrug, tenofovir disoproxil fumarate (TDF), are substrates of ATP-binding cassette (ABC) transporters that are functionally expressed in the placenta, namely P-glycoprotein (ABCB1/MDR1), Breast Cancer Resistance Protein (ABCG2/BCRP) and Multidrug Resistance-Associated Protein 2 (ABCC2/MRP2). We employed in-vitro cell-based assays and in-situ animal model to assess possible role of the efflux transporters in transplacental pharmacokinetics of TFV and TDF. METHODS: In-vitro transport assays were performed in MDCKII cells transduced with human ABCB1, ABCG2 or ABCC2. To quantify the effect of these transporters on TFV/TDF transplacental passage, we employed the in-situ model of dually perfused rat term placenta in open and closed setup. RESULTS: In-vitro assays revealed that TDF is a dual substrate of ABCB1 and ABCG2 but not of ABCC2. In contrast, TFV transport was not influenced by any of these transporters. Applying concentration-dependent studies and selective inhibitors, we further confirmed these findings in situ on the organ level; both ABCB1 and ABCG2 limited mother-to-fetus transfer of TDF whereas TFV transplacental passage was not affected by these ABC transporters. CONCLUSION: We propose limited mother-to-fetus transport of both TFV and TDF. While placental transport of TFV is restricted passively, by physical-chemical properties of the molecule, mother-to-fetus passage of TDF is actively hindered by placental ABCB1 and ABCG2 transporters, pumping this compound from trophoblast back to maternal circulation.
Keywords: Adenine; Cell Line; ABC transportér z rodiny G, člen 2; Neoplasm Proteins; Rats; protein spojený s mnohočetnou rezistencí k lékům 2; ATP-Binding Cassette Transporters; ATP Binding Cassette Transporter, Subfamily B, Member 1; nádorové proteiny; ATP Binding Cassette Transporter, Subfamily G, Member 2; Anti-HIV Agents; Rats, Wistar; Multidrug Resistance-Associated Protein 2; adenin; proteiny spojené s mnohočetnou rezistencí k lékům; ATP Binding Cassette Transporter, Subfamily B; P-glykoprotein; krysa rodu Rattus; Organophosphonates; ženské pohlaví; zvířata; Humans; Tenofovir; Multidrug Resistance-Associated Proteins; látky proti HIV; P-glykoproteiny; ABC transportéry; buněčné linie; potkani Wistar; Female; tenofovir; organofosfonáty; lidé; Animals